Melaleuca alternifolia: A SYSTEMATIC REVIEW OF BRAZILIAN LITERATURE - Ribeiro Nepomoceno, Taiane Aparecida; Pietrobon, Alex Junior (Uningá Review, 2020)
The Melaleuca alternifolia is a shrub originating of Australia, belonging the class of eudicotyledonous angiosperms. In recent years, its chemical composition and biological activities have been the subject of intense scientific analysis. Thus, this article aims to investigate how the studies on Melaleuca alternifolia in Brazil and their use in research areas conform. To this end, a review of the Brazilian literature was performed, with a systematic search in three electronic databases, namely: Scielo, web of Science and Google Scholar. Twenty years of production were selected, from 1999 to 2019. Were selected and analyzed for review 152 scientific papers. The Melaleuca alternifolia has been found to be an important medicinal plant in Brazilian studies, involving several thematic axes, such as agriculture, aquaculture and public health, for example. The systematic review also showed that it, besides being known in folk medicine, has been scientifically tested and expresses larvicidal, repellent, aromatic, insecticidal, antimicrobial, biocidal and antifungal activity.